(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تهدف هذه الدِّراسة إلى تحديد العلاقة بين أبعاد إدارة المعرفة والميزة التَّنافسيَّة في جامعة تشرين في اللَّاذقيَّة, من خلال معرفة دور كل من البعد التكنولوجي والبعد التنظيمي, والبعد الاجتماعي. وقد اعتمد الباحث على المقاربة الاستنباطيَّة كمنهج عام للبحث, واتباع منهجيَّة المسح، وقام بتوزيع الاستبانة على 319 فرد من كادر العاملين في الجامعة. وقد خلصت الدِّراسة إلى وجود علاقة معنوية طرديَّة مقبولة بين إدارة المعرفة والميزة التنافسية، حيث كانت النتيجة الرئيسة الأهم هي أنَّ هناك دوراً كبيراً لإدارة المعرفة في تحسين الميزة التَّنافسيَّة من خلال البعد التكنولوجي والبعد التنظيمي والبعد الاجتماعي. ثمَّ تمَّ عرض بعض المقترحات والتَّوصيات لتحسين هذه العلاقة، والتي أهمُّها: ضرورة أَنْ تزيد المنظَّمة من اهتمامها بإدارة المعرفة من خلال تحديث وتطوير الأجهزة والبرمجيات الخاصة بتكنلوجيا المعلومات باستمرار، وأن تواكب كل ما هو جديد وتهتم بمعرفة التكنولوجيا التي تستخدمها الجامعات المنافسة المحلية والخارجية، وأن تتوافر لديها شبكة اتصالات حديثة وفعالة لخدمة النظام داخل الجامعة، الأمر الذي يؤدي إلى إكسابها ميزة تنافسية بالمقارنة مع باقي الجامعات. This study aims to identify the relationship between the dimensions of knowledge management and competitive advantage at Tishreen University in Lattakia, by knowing the role of the technological dimension, the organizational dimension, and the social dimension. The researcher adopted the hypothetical approach as a general approach to research, and then conducted a field study On 319 members of the staff of the university staff. the study concluded that there is a significant positive relationship between knowledge management and competitive advantage, The main result was that there is a great role of knowledge management in improving the competitive advantage through the technological, organizational, and social dimension. The researcher recommends to increase the institution’s interest in knowledge management through modernization and development And to keep pace with all that is new and interested in the knowledge of technology used by the local and external competitive universities, and to have a modern and effective communication network to serve the system within the university. J leads to teaching them a competitive advantage when compared with other universities.